Use of systemic steroids during pulmonary exacerbations in children and adolescent with Cystic fibrosis - Danish Abdul Aziz; Siddique, Fatima; shahid, Shahira; Alam, Anusha; Aziz, Namrah (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the role of systemic steroids in cystic fibrosis patients and its effects on pulmonary exacerbation in children and adolescents. Method: The retrospective cohort study was conducted at the Aga Khan University Hospital, Karachi, and comprised data from January 2015 to December 2019 of cystic fibrosis patients aged 3-18 years hospitalised with pulmonary exacerbations. The patients were divided into systemic steroid group A and non-systemic steroid group B. Patients in group A received parenteral steroids during acute exacerbation of cystic fibrosis in the first two weeks of admission, while those in group B did not receive systemic steroids. Length of hospital stay and number of days on oxygen support were compared between the groups. Data was analysed using SPSS 22. Result: Of the 124 patient charts evaluated, 84(67.7%) were included; 40(47.6%) in group A and 44(52.4%) in group B. There were no significant differences between the groups related to age, age at diagnosis, weight, height, and pulmonary exacerbations (p>0.05). Group A had significantly fewer days on oxygen support compared to group B (p<0.001), but there was inter-group difference in mean length of hospital stay (p=0.53). Conclusion: Systemic steroid usage during hospitalisation for acute exacerbation of cystic fibrosis was associated with decreased duration of oxygen requirement with standard treatment. Key Words: Pulmonary exacerbation, Systemic corticosteroids, Oxygen support.